Short communication. Inhibition of Paenibacillus larvae subsp larvae by the eáential oils of two wild plants and their emulsifying agents - Fuselli, S.R.=700 1 Gende, L.B.; Garcia de la Rosa, S.B.; Eguaras, M.J.; Fritz, R.
(Es, En)
ilus., 35 ref.
Keywords: ABEJA MELIFERA; BACTERIOSIS; CONTROL DE ENFERMEDADES; INHIBICION; ACEITES ESENCIALES; MANZANILLA; TOMILLO; LECITINAS; ALCOHOLES; ESPAÑA; LOQUE AMERICANA; PAENIBACILLUS LARVAE